Perceived competency requirements for emergency medical services field supervisors in managing chemical and explosive incidents - qualitative interview study - Kauppila, Jussi; Iirola, Timo; Nordquist, Hilla (BMC, 2025)
Background Chemical, biological, radiological, nuclear, and explosive (CBRNE) incidents present rare and complex challenges for Emergency Medical Services (EMS), necessitating effective incident command to manage occupational and patient safety risks. EMS incident commanders must make quick decisions under pressure, coordinating medical responses and ensuring personnel's safety. This study examined the perceived competence requirements of Finnish EMS field supervisors in managing C and E incidents.
Methods This study was a qualitative interview study among EMS field supervisors (n = 12) in Southwest Finland. Individual interviews utilized fictional C and E case descriptions. The data was analyzed using inductive-deductive content analysis, with the Major Incident Medical Management and Support model as the theoretical framework.
Results The results were grouped under one inductive main category, "Being Prepared," and six deductive main categories: "Command and Control," "Safety," "Communication," "Assessment," "Triage and Treatment," and "Transport." Under the main categories, there were a total of 16 upper categories and 15 subcategories. Broadly similar content emerged from the C and E cases, although some categories had specific areas of emphasis.
Conclusions The perceived competence requirements of EMS field supervisors in managing C and E incidents align well with the Major Incident Medical Management and Support model. Also, EMS field supervisors should be mentally prepared and well-trained for handling C and E incidents. The results support the development of specific C and E training and guidelines beyond the "all hazards" approach. Further research should focus on assessing the current level and gaps in competence and optimizing training methods for different CBRNE situations.